PENGARUH HARGA, CITRA MEREK, PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PEDRO DI TANGERANG SELATAN - Dinda Ariny Weningtyas (2023)
Fashion has now become a part of people's needs and lifestyle. In the era of globalization, the development and contribution of the creative industry in the fashion sub-sector continues to increase. Men or women, young or old, all groups follow fashion developments and try to always look fashionable. However, the emergence of the Covid-19 pandemic has had a major impact on various industrial sectors, including the fashion industry, resulting in a sluggish market. Even though it had experienced a decline, the fashion industry was able to adapt quickly. Of the various fashion brands that have made it through the Covid-19 storm, one of them is Pedro. This study aims to see the effect of Price, Brand Image, and Promotion on the Purchase Decision of products from that brand. This study took a sample of 100 people who had purchased Pedro products. As a data management analysis tool, the authors use the SPSS 25 program to test the effect of each variable. From the results of statistical tests, it is known that Price, Brand Image, and Promotion have a partial and simultaneous effect on Purchasing Decisions.